Can atmospheric circulation be linked to flooding in Europe? - Christel Prudhomme; Marie Genevier (2011)
This paper evaluates whether circulation type catalogues (CTCs) can inform on the occurrence of floods in Europe, and if the same few circulation types (CTs) are systematically associated with floods at the European scale. A measure of the spatial coherence of CT was introduced to compare the relative performance of CTCs in discriminating flood events, based on a local indicator measuring if a CT occurs more frequently than usual prior/during a flood. Antecedent conditions and time-lag of catchments were accounted for in calculating the indicators on a range of durations up to 30 days preceding a flood. Relationships between flood occurrence on 488 river basins and CTCs were explored using 73 catalogues developed within COST733 Action, all defined from automatic algorithms using ERA-40 data. Results showed that at the river basin scale, some CTs have significant, positive frequency anomalies with flood occurrence. At the scale of Europe, the same CTs showed the strongest links with flood occurrence. The number of classes of CTCs is of lesser importance than the algorithm used, and depending whether global frequency or persistence of CT was analysed could give contrasting results. Results obtained from an automatically derived Grosswetterlagen classification were consistent with previous research, but performance was lower than that of other automatic algorithms (e.g. WLKC and SANDRAS). Results showed seasonal variation, possibly highlighting the differences in flood generation mechanisms in different regions and seasonal CT frequency. © 2010 John Wiley & Sons, Ltd.